Analysis of Village Financial Management Based on the Minister of Home Affairs Regulation No. 20 of 2018(Case Study in Bangun Rejo Village, Tanjung Morawa District) - Syifani Ashira; Puja Rizqy Ramadhan (PT FORMOSA CENDEKIA GLOBAL, 2024)
All activities including planning, implementation, administration, reporting and accountability of village funds are collectively referred to as village financial management. The purpose of this study was to determine how Bangun Rejo Village, Tanjung Morawa District, has implemented financial management in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018. The research methodology used is descriptive qualitative. Data collection techniques include documentation, interviews, and observations. The results of the study indicate that in general the procedures for financial management of Bangun Rejo Village are in accordance with the Regulation of the Minister of Home Affairs Number 20 of 2018